2016
DOI: 10.1021/acsomega.6b00281
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2-Tetrazolylmethyl-isoindolin-1-ones via a One-Pot Ugi-Azide/(N-Acylation/exo-Diels–Alder)/Dehydration Process

Abstract: A series of fifteen 2-tetrazolylmethyl-isoindolin-1-one linked-type bis-heterocycles were synthesized in 10–76% yields under mild conditions via a one-pot Ugi-azide/(N - acylation/ exo -Diels–Alder)/dehydration process from furan-2-ylmethanamine, aldehydes, isocyanides, azidotrimethylsilane, and maleic anhydride. Density functional theory calculations were performed using the polarizable continuum model (toluene)-M06-2X-D3/6-311+G(d)//M06-2X-D3/6-31G(d) level of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 47 publications
0
14
0
Order By: Relevance
“…The latter undergoes a decarboxylation to give 17 , followed by a dehydration to provide the pyrrolo[3,4- b ]pyridin-5-ones 11 (Scheme 6). It is worth noting that a close DFT-based study was reported recently by Gámez-Montaño et al to support a plausible reaction mechanism for the construction of the isoinsolin-1-one core via an Ugi-type reaction [29]. Besides, as was discussed, the pyrrolo[3,4- b ]pyridin-5-one is the ‘aza-version’ of the isoinsolin-1-one core.…”
Section: Resultsmentioning
confidence: 53%
“…The latter undergoes a decarboxylation to give 17 , followed by a dehydration to provide the pyrrolo[3,4- b ]pyridin-5-ones 11 (Scheme 6). It is worth noting that a close DFT-based study was reported recently by Gámez-Montaño et al to support a plausible reaction mechanism for the construction of the isoinsolin-1-one core via an Ugi-type reaction [29]. Besides, as was discussed, the pyrrolo[3,4- b ]pyridin-5-one is the ‘aza-version’ of the isoinsolin-1-one core.…”
Section: Resultsmentioning
confidence: 53%
“…Replacement of Tryptamine with furfurylamine in AU-4CR followed by sequential (N-acylation/exo-Diels-Alder)/dehydration reaction allowed the first one-pot synthetic path towards linked type BHCs containing 2-tetrazolylmethyl-isoindolin-1-one 97. [84] In the first step, the sequential addition of furfurylamine, aldehydes, isocyanides, and TMSN 3 in methanol solvent at room temperature afforded the AU-adduct 95. With the addition of Maleic anhydride, the N-acylation reaction of the amine group followed by subsequent Exo-Diels-Alder reaction with furan ring in 95 led to the formation of 96.…”
Section: Ugi-based Imcrs For the Synthesis Of Spacer-linked Bhcsmentioning
confidence: 99%
“…Our ongoing research program focuses on the design of new or novel, rapid, convergent, ecofriendly, and efficient post-IMCR/transformation strategies in consecutive [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] or domino manner [ 39 , 40 , 41 ] toward the synthesis of novel molecules containing conformationally restricted and/or constrained peptidomimetics. Recently, we reported the first ultrasound-assisted green one-pot synthesis of molecules containing privileged restricted peptidomimetics via this strategy: post-IMCR transformation/ Copper(I)-catalyzed azide-alkyne cycloaddition (CuAAC) click reaction employing a green alternative energy source [ 42 ].…”
Section: Introductionmentioning
confidence: 99%